The non-existence of God - Everitt, Nicholas, 1943- (Toronto Studies in Theology, 2004)
Arguments for the existence of God have taken many different forms over the centuries: in The Non-Existence of God, Everitt considers all the arguments and examines the role that reason and knowledge play in the debate over God's existence.